2007
DOI: 10.1080/09638280600835994
|View full text |Cite
|
Sign up to set email alerts
|

From childhood to adult life with juvenile idiopathic arthritis (JIA): A pilot study

Abstract: This pilot study has identified inadequacies in the transition management provided for young people with JIA. Acceptance of the young persons as active participants in their own transition process might strengthen these young persons' experience of an autonomous identity and enable participation socially and in society, thus enhancing the ability to achieve a meaningful adult life. Further investigations should focus on adults living with JIA, how they lead their lives physically and psychosocially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 17 publications
1
26
0
5
Order By: Relevance
“…(2014) also concluded that young people, in general, appreciated the transition as a step forward; however, they felt inadequately prepared for the transition. This is in line with both our findings and other studies indicating that it is challenging to manage the transition as well as the new framework of adult care services when preparation of the transition is inadequate (Östlie et al., 2007; Shaw et al., 2004; van Staa et al., 2011). Part of the preparation might be remedied by information in both child and adult care to clarify differences in organisation and procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2014) also concluded that young people, in general, appreciated the transition as a step forward; however, they felt inadequately prepared for the transition. This is in line with both our findings and other studies indicating that it is challenging to manage the transition as well as the new framework of adult care services when preparation of the transition is inadequate (Östlie et al., 2007; Shaw et al., 2004; van Staa et al., 2011). Part of the preparation might be remedied by information in both child and adult care to clarify differences in organisation and procedures.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with others and underpins that adolescents generally find it positive to become more responsible and take more control of their disease and see the positive aspects of being considered as a responsible adult (Kirk, 2008; Shaw et al., 2004; van Staa et al., 2011; Östlie et al., 2007). Furthermore, Fegran et al.…”
Section: Discussionmentioning
confidence: 99%
“…Dette er i overensstemmelse med funnene fra andre studier (21,25). Fysioterapeuter og ergoterapeuter ser ut til å vaere de helseprofesjonene som hadde et budskap som var tydelig for de unge.…”
Section: Resultaterunclassified
“…Det interessante i denne studien er hvor lite informantene kan huske å ha fått av råd og veiledning om temaer som har å gjøre med livet som ungdom og som fremtidig ung voksen, og hvem som i tilfelle ga slik råd og veiledning. I en tidligere studie (21) kom det frem at helsepersonell mente at de hadde gitt råd og veiledning når de syntes det var naturlig, men mer uformelt og uten noen omforent plan eller strategi. Videre uttrykte helsepersonell i barnerevmatologien om seg selv at de startet for sent og overlot for lite ansvar til den unge selv (21).…”
Section: Resultaterunclassified
See 1 more Smart Citation